Peningkatan Produktivitas Lahan dan Pendapatan Petani Melalui Tanaman Sela Pangan Berbasis Karet - Sahuri Sahuri (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Sahuri et al, 2017. Increasing of Land Productivity and Smallholders Income through Rubber Based Food Crops Intercropping System. JLSO 6(1):33-42.The land between a row of immature rubber period has a potential to produce food crops. The objective of this research was to study the effect of rubber+food crops intercropping system on increasing the land productivity of rubber, the growth of immature rubber trees and smallholders income. The experiment was conducted at the Sembawa Research Station from September 2013 to April 2014. The experiment was carried out as using randomized block design (RBCD). The treatments were four-planting patterni.e: PT1: rubber+upland rice; PT2: rubber+sweet corn; PT3: rubber+soybean; and PT4: rubber monoculture, with three replications.The results showed that food crops as rubber intercrops significantlyeffect on increasing the land productivity of rubber andthe growth of rubber. The added value of planting food crops as rubber intercrops are the efficiency of farming cost and farmer income increase of IDR 4,318,300/planting season/ha with RC ratio 1.38. Farmers have food availability for daily needs during the second year of immature rubber period.